Frutíferas de uso múltiplo em quintais agroflorestais na comunidade indígena de Filadélfia, município de Benjamin Constant – AM - Bastos, Keonys Pereira (Brasil, 2025)
The Amazon has a wide diversity of plant species, among which fruit trees are the result of the domestication process carried out by traditional populations, who over time have developed their own knowledge about cultivation, management and different forms of use. The aim of this research was to carry out a survey of multiple-use fruit species in Ticuna agroforestry backyards in the community of Filadélfia, in the municipality of Benjamin Constant, Amazonas. The study area was the Philadelphia indigenous community, specifically in the agroforestry backyards. The data was collected using qualitative-quantitative research of a descriptive and exploratory nature, using field techniques such as on-site observation, a guided walk or tour for rapid diagnosis, accompanied by a key informant, defined by the snowball technique, and the application of a semi-structured interview form. The data collected was subjected to descriptive statistics and transformed into charts, tables and percentages. The results showed that the farmers in the Philadelphia Indigenous Community are of one gender (50% female and 50% male) and have a predominant age range of between 50 and 75 years. The majority belong to the Ticuna ethnic group (92.9%). The diversity of fruit species in the backyards is significant, with 97 individuals distributed in 43 botanical families, with the Arecaceae family standing out. Fruit trees are crucial for food and nutritional security, as well as being used for medicinal, craft and shading purposes. Farmers face challenges such as lack of access to technology and inadequate infrastructure. Fruit species are therefore important for food security and sustainability. The diversity of species and associated knowledge are essential for maintaining food needs and contributing to the quality of life of families in the community. Agroforestry farms (QAFs) stand out as crucial spaces for family farming, agro-biodiversity conservation and traditional knowledge. They reflect the way of life of local populations, being an extension of their homes and promoting food security and environmental conservation. In addition, QAFs represent ancient practices of sustainable land management, demonstrating resilience and sustainability over time. The management of QAFs involves planning, knowledge, collective work, respect for nature and neighbours, and is based on experience and knowledge passed down between generations. These practices strengthen community ties and cultural identity, while playing a significant role in the local economy, creating jobs and ensuring the food security and health of residents. Therefore, the preservation of QAFs is vital to the economic, social and cultural well-being of the indigenous community of Philadelphia, guaranteeing the sustainability and continuity of the traditional practices that sustain community life.